Chrysin-based supramolecular cyclodextrin-calixarene drug delivery system: a novel approach for attenuating cardiac fibrosis in chronic diabetes - Trotta, Maria Consiglia; Herman, Hildegard; Ciceu, Alina; Mladin, Bianca; Rosu, Marcel; Lepre, Caterina Claudia; Russo, Marina; Bácskay, Ildikó; Fenyvesi, Ferenc; Marfella, Raffaele; Hermenean, Anca; Balta, Cornel; et al. (Frontiers in Pharmacology, 2023)
Introduction: Cardiac fibrosis is strongly induced by diabetic conditions. Both chrysin (CHR) and calixarene OTX008, a specific inhibitor of galectin 1 (Gal-1), seem able to reduce transforming growth factor beta (TGF-β) / SMAD pro-fibrotic pathways, but their use is limited to their low solubility. Therefore, we formulated a dual-action supramolecular system, combining CHR with sulfobutylated β-cyclodextrin (SBECD) and OTX008 (SBECD+OTX+CHR). Here we aimed to test the anti-fibrotic effects of SBECD+OTX+CHR in hyperglycemic H9c2 cardiomyocytes and in a mouse model of chronic diabetes.Methods: H9c2 cardiomyocytes were exposed to normal (NG, 5.5 mM) or high glucose (HG, 33 mM) for 48 hours, then treated with SBECD+OTX+CHR (containing OTX008 0.75-1.25-2.5 µM) or the single compounds for 6 days. TGF-β/SMAD pathways, Mitogen-Activated Protein Kinases (MAPKs) and Gal-1 levels were assayed by Enzyme-Linked Immunosorbent Assays (ELISAs) or Real-Time Quantitative Reverse Transcription Polymerase chain reaction (qRT-PCR). Adult CD1 male mice received a single intraperitoneal (i.p.) administration of streptozotocin (STZ) at a dosage of 102 mg/kg body weight. From the second week of diabetes, mice received 2 times/week the following i.p. treatments: OTX (5 mg/kg)-SBECD; OTX (5 mg/kg)-SBECD-CHR, SBECD-CHR, SBECD. After a twentytwo-week period of diabetes, mice were euthanized and cardiac tissue used for tissue staining, ELISA, qRT-PCR aimed to analyse TGF-β/SMAD, extracellular matrix (ECM) components and Gal-1.In H9c2 cells exposed to HG, SBECD+OTX+CHR significantly ameliorated the damaged morphology and reduced TGF-β1, its receptors (TGFβR1 and TGFβR2), SMAD2/4, MAPKs and Gal-1. Accordingly, these markers were reduced also in cardiac tissue from chronic diabetes, in which an amelioration of cardiac remodeling and ECM was evident. In both settings, SBECD+OTX+CHR was the most effective treatment compared to the other ones.The CHR-based supramolecular SBECD-calixarene drug delivery system, by enhancing the solubility and the bioavailability of both CHR and calixarene OTX008, and by combining their effects, showed a strong anti-fibrotic activity in rat cardiomyocytes and in cardiac tissue from mice with chronic diabetes. Also an improved cardiac tissue remodeling was evident. Therefore, new drug delivery system, which could be considered as a novel putative therapeutic strategy for the treatment of diabetes-induced cardiac fibrosis.